Studium als Balanceakt Lebensführung von erwerbstätigen First-in-Family Studierenden - Lessky, Franziska (2023)
This open access book sheds light on study-related experiences of First-in-Family students in Austria. For the first time, this book comprehensively illuminates those areas of life in which students are embedded outside of the university environment. The analysis focuses on the reconstruction of first-in-family students' agency and capitals.